Quantitative assessment on the epidemic characteristics of severe fever with thrombocytopenia syndrome virus infection in China - Shengyao Jiang; Mian Khaqan Shah; Li Cui (Elsevier, 2021)
Severe fever with thrombocytopenia syndrome (SFTS) was first detected in China in 2009. The incidence of SFTS increases year by year, and there is no effective treatment. Considering that the reported prevalence of SFTSV infection varies from region to region, we aimed to quantitatively evaluate the epidemic characteristics of SFTSV infection in China from 2010 to 2020, including the distribution differences in infectious season, sex, age, occupation, and region. A meta-analysis framework was used to search for the related published data with keywords in electronic databases (CNKI, WanFang, CBM, and PubMed). According to the PRISMA statement, the studies that included SFTS diagnosed in China were analyzed. Furthermore, we used Revman and Stata to merge statistical effects, and used I2 and P-values for heterogeneity test and quality assessment. Eleven studies containing 4,932 cases confirmed by SFTSV infection were included in this meta-analysis. The ratio of male-to-female is 1.04 to 1. Cases were concentrated between 40 and 80 years of age (MD = 92%, 95%CI: 91%-93%). Farmers are at the highest risk of SFTSV infection (MD = 84%, 95%CI: 77%-90%). The risk of infection for consecutive period of April-August was significantly higher than the sum of the remaining months (MD = 82%, 95%CI: 78%-85%). In addition, the patient has an extensive history of exposure, including living in the mountains, exposure to ticks, livestock, mouse and the patient. We came to the conclusion that SFTSV is transmitted primarily through tick bites in China, so middle-aged and older adults living in mountains regions are at the highest risk for SFTSV infection in April through August each year.